Pengaruh Pemberian Makanan Singkong Rebus, Talas Kukus Dan Jagung Rebus Sebagai Alternatif Makanan Pencegahan Gastritis Di Tanjung Kemuning Iii Kecamatan Tanjung Kemuning Kabupaten Kaur - Ansyorollah Ansyorollah; Asih Apriyani; Dewi Syartika Putri; Dewi Harmili; Pirda Maya Tika; Rita Amila; Yusran Fauzi; Julius Habibi (Utami Publisher, 2026)
Gastritis is a common digestive disorder. According to the World Health Organization (WHO), gastritis is an inflammation of the gastric mucosa that can be acute or chronic. Robbins & Cotran explain that gastritis occurs due to mucosal inflammation triggered by various factors such as Helicobacter pylori infection, alcohol, stress, and non-steroidal anti-inflammatory drugs (NSAIDs). Globally, gastritis remains a significant health problem. In 2021, an estimated 27.20 million people worldwide were living with gastritis and duodenitis, with an incidence rate of 323.24 per 100,000. Meanwhile, in Indonesia, gastritis is a digestive system disease with a relatively high prevalence. National data shows that the prevalence of gastritis has been reported to reach 40.8% of the population. In the context of public health, the incidence of gastritis is significantly influenced by diet, particularly the consumption of foods that can irritate the stomach. Local food is food produced, processed, and consumed locally, such as traditional foods made from tubers, local agricultural products, and traditional dishes. Local food consumption patterns are often influenced by customs, culture, and food availability. While some local foods are healthy and support digestive function, others can trigger stomach irritation if consumed in excess or prepared improperly, such as if they are too spicy, sour, fatty, or fried repeatedly. Therefore, based on existing data, an outreach program on gastritis was conducted in Tanjung Kemuning III Village, targeting the community